Beyond the twelve-factor app : exploring the DNA of highly scalable, resilient cloud applications - Hoffman, Kevin, 1975- (O'Reilly Media, 2016)
In 2012, early cloud pioneer Heroku developed the Twelve Factor App, a set of rules and guidelines for helping organizations build cloud-native applications. It served as an excellent starting point, but as technology inevitably marched forward, some areas needed revisiting. To accommodate current best practices, this practical book expands on the original guidelines to help you build applications that not only function in the cloud, but also thrive . Information architect Kevin Hoffman takes you through each factor in detail, explaining why these guidelines are important and, in some cases, pointing out how and why today's new approaches work better. You'll learn exactly what a 12 factor app is, and discover how to evaluate your existing applications against the guidelines in this book. Compare the original 12 factors to the author's 15 expanded and revised factors Understand why the concept of "API First", as well telemetry and security have been added Learn the caveats or exceptions to the original factors that reflect today's best practices